DATING AND CORRELATION OF THE BALUTI FORMATION, KURDISTAN, IRAQ: Implications for the regional recognition of a Carnian "marker dolomite", and a review of the Triassic to Early Jurassic sequence stratigraphy of the Arabian Plate. (10th December 2018) - Lunn, G. A.; Miller, S.; Samarrai, A.
Abstract : The Baluti Formation is a lithostratigraphic unit defined at outcrop in the Zagros foldbelt in Kurdistan, North Iraq, where it consists of a thin, shale‐dominated interval between the thick carbonates of the overlying Sarki and the underlying Kurra Chine Formations. New biostratigraphic results presented in this study confirm that firstly, the Baluti shale marks the top of the Carnian at outcrop; and secondly, that the correlative subsurface shale occurs well above the base of the subsurface‐defined Butmah Formation. As such, the Butmah is not directly correlative to the Sarki as has previously been assumed, and its definition overlaps that of the Baluti and Kurra Chine Formations. These results have regional implications. A distinctive low Gamma Ray dolostone unit in the Kurra Chine A can be correlated across Kurdistan. Similar dolostones are recognised widely across the Arabian Plate and have been considered to be correlative by some workers, but not by others. This study establishes the age of this "Marker Dolomite" as late Carnian on the basis of its position below the Baluti Formation and confirms its regional development. Correlation is demonstrated to the Sefidar Dolomite (Iran), the "Muss"/Mulussa D (Syria), the upper Abu Ruweis Formation (Jordan), the Jilh Formation (Kuwait, Saudi Arabia, Oman), and the upper Gulailah Formation (UAE). Regional sequence stratigraphic studies have assigned the Marker Dolomite to different sequences in different areas. The recognition that it represents a single, regionally‐correlatable event provides the starting point for a sequence stratigraphic review based on regional log correlation and published dating. An updated sequence stratigraphic framework is presented for the Triassic to Early Jurassic, defining additional sequences (e.g. Tr55, Tr90, Tr100, J01, J05) and recognising that significant depositional breaks are associated with SBs Tr60, Tr70, Tr80, Tr100 and J01. The hiatus below Tr80 reflects a Carnian–Ladinian regional high in the Southern Gulf. This represents the barrier between the open Neo‐Tethys and the saltern in which the Carnian evaporites accumulated. The implications for petroleum exploration are discussed in the light of these revisions. There are two established Triassic plays in Iraq and Syria: firstly, in fractured carbonate reservoirs sealed by evaporites and shales, which is productive in both countries; and secondly, in fluvial sandstones sealed by interbedded shales, which is productive in Syria. A key observation regarding the carbonate play is that the main Triassic exploration target in Iraq has been the Kurra Chine B fractured carbonates, located above the main Carnian evaporites; whereas in the Syrian Palmyrides, the main discoveries are generally located below the Carnian evaporites. The sub‐evaporite fractured carbonate play is underexplored in Iraq. With regard to the clastic play, the correlations presented in this study indicate that the Mulussa F and Minjur represent a single clastic pulse, and equivalent sandstones are likely to be developed in the Sarki Formation in Central‐South Iraq which remains largely untested. Sequence correlations indicate regionally developed source rock potential at the levels of the Kurra Chine B Member and Geli Khana Formation.